French Language Services in Home Care: Final Report presented to the PEI French Health Network - Atlantic Evaluation Group Inc. (2013)
The French Language Services in home care Research Project was initiated by the PEI French Health Network (PEIFHN), and is part of the Network's ongoing work with respect to strengthening the delivery of French language services. The Project was designed to conduct background research into the nature and scope of needs of an aging Francophone population, with a particular focus on residents who require home care services to support them to remain in their home, and home community for as long as possible. The overall intent is to identify possible service delivery methods and approaches that could strengthen the delivery of French language services within the province's Home Care Program. The primary research activities included: a review of the latest Census data to describe the current profile and distribution of the Island's Francophone population by Francophone region; a review of relevant health care documents and reports; a series of community consultations; interviews and consultation sessions with home care managers and staff; an interview with the Public Health Nurse at the Evangeline Health Care Centre in Wellington; and an interview with a Francophone Family Physician. Recommendations are being made to ensure a more visible and consistent provision of French language services.
pages: 53

Soins à domicile en français. Rapport final présenté au Réseau Santé en français Î.-P.-É. - Atlantic Evaluation Group Inc (2013)
Le Projet de recherche sur les soins à domicile en français a été amorcé par le Réseau Santé en français Î.-P.-É. (RSFÎPÉ) et fait partie du travail soutenu accompli par le réseau en vue d’améliorer la prestation des services en français. Le Projet visait la réalisation de recherches préliminaires sur la nature et l’étendue des besoins d’une population francophone vieillissante, notamment des résidents qui nécessitent des soins à domicile en vue de les aider à demeurer chez eux et dans leur communauté le plus longtemps possible. L’objectif général est de cerner des approches et des méthodes potentielles qui pourraient améliorer la prestation de services en français dans le cadre du programme de soins à domicile de la province. Les principales activités de recherche comprenaient : une analyse des dernières données du recensement afin de cerner le profil actuel et la répartition de la population francophone de l’Île par région francophone; un examen des documents et rapports pertinents en matière de soins de santé; une série de consultations communautaires; des entrevues et des séances de consultation avec les gestionnaires et le personnel des services à domicile; une entrevue avec l’infirmière de la santé publique au centre de soins de santé Évangéline de Wellington; et une entrevue avec un médecin de famille francophone. Des recommandations sont émises pour une offre plus visible et constante de services en français.
Nombre de pages: 65

The health impact of living in a nursing home with a predominantly different spoken language: Lettor to the Editor - Batista, Ricardo; Prud’homme, Denis; Hsu, Amy T.; Guérin, Eva; Bouchard, Louise; Rhodes, Emily; Talarico, Robert; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2019)
Abundant research shows that linguistic barriers can have a negative impact on access to and quality of health care, as well as a patient's health outcomes. Establishing a culturally appropriate environment, by providing care to nursing home residents in their preferred language, is key in providing good-quality long-term care (LTC) services. French is one of Canada's 2 official languages. In Ontario, Canada, studies using population-based data have shown that Francophones have a lower perception of good health, higher prevalence of chronic diseases, and greater dependency on LTC services compared to Anglophones. However, the impact of language discordance on the outcomes of residents in nursing homes has not been previously explored. We conducted a population-based retrospective cohort study to assess the impact of language discordance on hospitalizations, emergency department (ED) visits, and mortality in a cohort of 122,416 incident admissions to nursing homes in Ontario between 2010 and 2016.

Do chronically ill, elderly Francophone patients believe they are adequately served by Ontario’s health care system? Exploratory study of the effect of minority-language communities - Bouchard, Louise; Chomienne, Marie-Hélène; Benoit, Monique; Boudreau, Françoise; Lemonde, Manon; Dufour, Suzanne (Canadian Family Physician, 2012)
In an exploratory study conducted on behalf of the Consortium national de formation en santé, a Canada-wide umbrella organization bringing together 11 postsecondary institutions that deliver training programs in various health disciplines in French, our research team explored the effect of language barriers perceived by elderly Francophone patients living in 3 different regions of Ontario with one or more chronic diseases. Our study was based on semistructured interviews of 25 elderly subjects (13 men and 12 women) with chronic diseases. It enabled us to determine the effect on the perception of the quality of care received by this Francophone population in relation to the challenges of language and literacy.

Les Franco-Ontariens âgés souffrant de maladies chroniques se perçoivent-ils bien desservis ? Une étude exploratoire de l'impact de la situation linguistique minoritaire - Bouchard, Louise; Chomienne, Marie-Hélène; Benoit, Monique; Boudreau, Françoise; Lemonde, Manon; Dufour, Suzanne (Le médecin de famille canadien, 2012)
Dans une étude exploratoire pour le compte du Consortium national de formation en santé, nous avons exploré l’impact des barrières linguistiques perçu par des personnes âgées francophones vivant en Ontario dans 3 régions différentes et souffrant d’une ou de plusieurs maladies chroniques. Notre étude, basée sur des entrevues semi-dirigées auprès de 25 personnes âgées (13 hommes et 12 femmes) souffrant de maladies chroniques, nous a permis de cerner des impacts particuliers sur la perception de la qualité des soins reçus par cette population en rapport aux enjeux de langue et de littératie.

Promoting the health and well-being of English-speaking Seniors in Quebec. A community model (infographic) - Community Health And Social Services Network / Réseau communautaire de santé et de services sociaux (2019)
fs-ref-orig: Community Health And Social Services Network. (2019). Promoting the health and well-being of English-speaking Seniors in Quebec. A community model [infographic]. fs-code-orig: Community Health And Social Services Network-2019

Agir pour avoir accès à des services sociaux et de santé en français. Des francophones en situation minoritaire nous enseignent quoi faire! - Drolet, Marie; Arcand, Isabelle; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien; Lagacé, Josée (Revue canadienne de service social / Canadian Social Work Review, 2015)
Même si les droits des francophones de l’Ontario sont garantis par la Loi de 1986 sur les services en français, l’accès à des services sociaux et de santé en français dans cette province s’avère complexe en raison d’importantes barrières à recevoir de tels services sur un continuum. Nous avons exploré à l’aide d’entrevues qualitatives les points de vue de 40 parents et proches aidants francophones qui vivent en contexte bilingue dans la région d’Ottawa et dont l’enfant ou l’aîné pour lequel ils ont une responsabilité d’aidant utilise des services sociaux et de santé en français. Ces francophones s’avèrent des acteurs au sein de leur trajectoire de services, adoptant cinq stratégies pour accéder à de tels services. De plus, le sentiment de confort et la relation de confiance que procure l’usage du français tout au long de l’intervention, ainsi que le soutien des professionnels francophones ont facilité leur démarche. Il n’en demeure pas moins que l’offre de services en français ne doit pas devenir la responsabilité d’individus ou d’une minorité. Mots-clés : Francophonie en situation minoritaire, accès à des services sociaux, minorité linguistique, barrières aux services, offre active de services en français, entrevues qualitatives

Health services for linguistic minorities in a bilingual setting: Challenges for bilingual professionals - Drolet, Marie; Savard, Jacinthe; Benoît, Josée; Arcand, Isabelle; Savard, Sébastien; Lagacé, Josée; Lauzon, S.; Dubouloz, Claire-Jehanne (Qualitative Health Research, 2014)
We explore in this qualitative research the challenges faced by bilingual health and social services professionals in a Canadian bilingual setting, as well as the strategies used to overcome them. Eight focus groups were conducted with a total of 43 bilingual Francophone professionals who offered services in French in 21 health and social service organizations in eastern Ontario, Canada. We highlight linguistic issues affecting a minority Francophone clientele, the shortage of services in French, and organizational issues within these agencies. The solutions that the professionals adopt for better serving the clients and overcoming these challenges focus on adapting services from linguistic angles. In the long term, such an enhanced approach can affect staff well-being. Ensuring access to services for linguistic minority populations and the active offer of same should not rest solely on the shoulders of such professionals, but rather on organizational strategies.

L’expérience des francophones dans l’Est ontarien : importance des personnes pivots (usagers et intervenants) et influence des structures encadrant le système de santé et des services sociaux - Drolet, Marie; Savard, Jacinthe; Savard, Sébastien; Lagacé, Josée; Arcand, Isabelle; Kubina, Lucy-Ann; Benoît, Josée (Accessibilité et offre active : santé et services sociaux en contexte linguistique minoritaire, 2017)
Résumé Le présent chapitre décrit l’expérience d’accès à des services sociaux et de santé en français de francophones de l’Est ontarien. Les expériences et les perspectives de 40 parents, aînés et proches aidants ont été recueillies à l’aide d’entrevues semi-structurées. Une analyse qualitative des verbatim ainsi qu’une analyse visuelle des trajectoires d’un sous-groupe de neuf participants ont permis de faire ressortir les facilitateurs et les défis d’accès aux services en français rencontrés par ces usagers, à partir de leur perspective ou de celle de leur proche aidant. Plus spécifiquement, ce chapitre met l’accent sur les éléments facilitateurs dans le but d’en tirer des leçons pour améliorer les services sociaux et de santé en langue officielle en situation minoritaire. Mots-clés : accès aux services en français, francophones Ontario, recherche qualitative.
Chapitre 6

The experience of Francophones in Eastern Ontario: The importance of key facilitators (service users and providers) and the influence of structures supporting the health and social services system - Drolet, Marie; Savard, Jacinthe; Savard, Sébastien; Lagacé, Josée; Arcand, Isabelle; Kubina, Lucy-Ann; Benoît, Josée (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
This chapter describes the experiences of Francophones in eastern Ontario in terms of access to social services and health care. The experiences and perspectives of 40 parents, seniors, and caregivers were collected through semi-structured interviews. Qualitative analysis of the transcripts, as well as visual analysis of the trajectories of a subgroup of nine participants, made it possible to identify facilitators and challenges these users experienced in accessing Frenchlanguage services, either from their perspective or that of their caregivers. More specifically, this chapter emphasizes elements that facilitate access; these are discussed in order to share the lessons learned, which can contribute to improvements in social services and health care in official language minority communities. Key Words: access to services in French, Ontario Francophones, qualitative analysis.
Chapter 6

Vieillir en santé en situation minoritaire linguistique au Canada : enjeux, defis et mobilisation collective - Dupuis-Blanchard, Suzanne; Villalon, Lita; Alimezelli, Hubert Tote (Global Health Promotion, 2014)
Au Canada, la santé des francophones et des anglophones vivant en milieu linguistique minoritaire est un sujet d’intérêt pour plusieurs chercheurs et organismes communautaires. Cet article s’inspire d’un symposium sur le thème concernant le vieillissement en santé en situation minoritaire linguistique présentée lors du 4e Colloque international des programmes locaux et régionaux de santé. Trois volets sont présentés, soit l’identification des facteurs associés à la santé perçue, le maintien à domicile et le dépistage de la malnutrition. Les résultats décrivent 1) les déterminants de la santé perçue tels que les services de santé, la vitalité de la communauté minoritaire et l’éducation ; 2) le peu de changements aux services de maintien à domicile en dépit du vieillissement de la population ; et 3) la haute prévalence de la malnutrition chez les aînés au Nouveau-Brunswick. Enfin, nous suggérons l’élaboration et l’implantation d’une politique publique du vieillissement au Canada afin d’assurer des services de qualité tout au long du continuum santé.

Case studies: Primary health service delivery models for the Francophone minority - Entités de planification des services de santé en français 1 et 2(Érié St. Clair / Sud-Ouest et WaterlooWellington, Hamilton, Niagara, Haldimand Brant) Et le Réseau Franco - Santé du Sud de l’Ontario (2016)
In several regions of the province, Francophones are in a minority situation. In several places, health services in French are minimal or even non-existent. Many stakeholders are trying to find solutions to improve or implement health services in French. Often these solutions are not always easy to identify or put in place. In this context, the Erie St. Clair/SouthWest French Language Health Planning Entity has used the services of a consultant who did an analysis of best practices in minority situations across North America and in other countries. This first analysis consists of a brief description of 352 practices developed to meet the needs of minority populations receiving few, if any, health services in their communities. Following this report, we have continued this research jointly with the Waterloo Wellington, Hamilton, Niagara, Haldimand Brant Entity2 and the French Health Network of Central Southwestern Ontario. Our purpose was to be able to identify 5 or 6 best practices in minority situations that might be applicable in our respective regions under the subject areas: primary health care, seniors care, mental illness and chronic disease. Each of the partners could study identified practices and ask more detailed explanations on certain practices that seemed more appropriate to respond to their local needs.
pages:

Forum on Partnering for Innovative and Collaborative Long-Term Care Solutions for Francophones - Fondation Hélène Tremblay Lavoie Foundation; Reflet Salvéo (Fondation Hélène Tremblay Lavoie Foundation, 2019)
Access to French Language Services, more specifically to long term care beds and specialized dementia care units are not equitable and accessible across the Greater Toronto Area (GTA) and do not meet the specific needs of the Francophones in terms of location and language needs. Based on the goals of laying the foundation for action-oriented public / private / not-for-profit partnerships (social enterprise), better defining the needs of the Francophone community for specialized long-term care, and exploring innovative models that can be adapted to the different needs of the community, Fondation Hélène Tremblay Lavoie Foundation organized a one-day Forum to engage with different stakeholders on November 23, 2018 in Toronto. The one-day Forum ensured that key stakeholders, namely private/public sector, seniors, caregivers, health and social service providers, long-term care homes, retirement homes, financial institutions, developers and governments (LHINs, ministries, GTA municipalities), French Language Services Planning Entities (Reflet Salvéo and Entité 4) and post-secondary educational institutions such as Collège Boréal, Glendon, UOIT, York and Schulich and University of Toronto) came together to discuss on opportunities to - create an awareness of different programs and care models within the French community - facilitate access to and expansion of French health care services and programs for Francophone adults experiencing loss of autonomy - raise funds to support the improvement of long-term care and for an eventual capital project to support building the first bilingual long-term care facility dedicated to serving Francophone adults experiencing loss of autonomy within the GTA. This one-day engagement provided an opportunity for stakeholders the opportunity to make recommendations on moving forward. As such, 13 recommendations have developed for different stakeholders including the Francophone community.

Les conditions favorables à l’établissement de services de santé pour les aînés francophones - Forgues, Éric; Couturier, Yves; Deroche, Francine (Institut canadien de recherche sur les minorités linguistiques et Société Santé en français, 2014)

La prise en compte de la langue dans les foyers de soins pour personnes âgées - Forgues, Éric; Gaucher, Charles; Guignard Noël, Josée; Kabano, John; Michaud, Jacques (Institut canadien de recherche sur les minorités linguistiques, 2012)

Health and social services for Francophone seniors in Eastern Ontario and Manitoba: Guidelines to improve the continuity of French language services. Research Report. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (Grefops), 2018)

Health and social services for Francophone seniors in Eastern Ontario and Manitoba: Guidelines to improve the continuity of French language services. Research Report - Summary. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (Grefops), 2018)

Les services sociaux et de santé pour les personnes âgées francophones de l’Est ontarien et du Manitoba : lignes directrices pour améliorer la continuité des services en français - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation professionnelle en santé et service social en contexte francophone minoritaire, 2018)

Les services sociaux et de santé pour les personnes âgées francophones de l’Est ontarien et du Manitoba : lignes directrices pour améliorer la continuité des services en français. Rapport de recherche - Résumé. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation professionnelle en santé et service social en contexte francophone minoritaire, 2018)

Promoting the health and well-being of English-speaking seniors in Quebec. A community model - Kueber, Rusell (Community Health and Social Services Network / Réseau communautaire de santé et de services sociaux, 2019)

Promotion de la santé et du bien-être des aînés d’expression anglaise du Québec : un modèle communautaire - Kueber, Russell (Réseau communautaire de santé et de services sociaux / Community Health and Social Services Network, 2019)

Language and culture in the caregiving of people with dementia in care homes - What are the implications for well-being? A scoping review with a Welsh perspective - Martin, Conor; Woods, Bob; Williams, Siôn (Journal of Cross-Cultural Gerontology, 2019)
The loss of language skills is one of the most challenging aspects of living with dementia. This is particularly true for bilingual individuals, who have difficulty in maintaining fluency in more than one language. Language and culture overlap greatly, with potential implications for the well-being of people with dementia (PWD) being cared for in their ‘second’ language or culture. Our aim was to review the available relevant literature, together with an examination of the potential effects of linguistic incongruity on healthcare in general for Welsh speakers in Wales. A literature search yielded 50 articles, which were analysed using the scoping review methodological framework. We found that the presence of cultural and linguistic congruity was beneficial for PWD living in care homes, and that their absence was detrimental. The absence of linguistic congruity is a strong predictor for decreased well-being in people in such settings, due to communication barriers between residents and carers, which result mainly from the loss of PWD’s second language skills. Such barriers may lead to inappropriate care, e.g. being unable to obtain help to self-care, as well as social isolation. This review suggests that strategies need to be developed across the world to accommodate bilingual individuals requiring a care home for their dementia needs. There is a particular dearth of research regarding the influence of bilingualism on the experience of dementia care in those areas of the UK where the indigenous population are most likely to be bilingual (i.e. parts of Wales).

Soins de longue durée en français. Rapport final au Réseau Santé en français Î.-P.-É. - McQuaid, Steve (Atlantic Evaluation Group Inc, 2010)
Nombre de pages: 48

La prise en compte du français dans l’organisation des services en foyers de soins majoritairement anglophones au Canada - Michaud, Jacques; Forgues, Éric; Guignard Noël, Josée (Minorités linguistiques et société, 2015)
L’accès aux services de santé en français préoccupe grandement les communautés francophones vivant en situation minoritaire. Le présent article offre un survol de l’espace francophone dans les résidences collectives d’aînés du Nouveau-Brunswick, de la Nouvelle-Écosse et de l’Ontario à la lumière d’une recherche exploratoire menée en 2012. L’analyse des données obtenues auprès d’aînés, d’aidants et du personnel, l’examen de la répartition géographique des résidences et de la population d’aînés francophones, ainsi qu’un aperçu du contexte réglementaire encadrant le fonctionnement de ces résidences permettent de définir la problématique pertinente. Des actions en vue d’améliorer la situation sont examinées. Mots-clés : espace francophone, services de santé en français, francophones en situation minoritaire, foyers de soins, résidences collectives, vieillissement de la population

Enabling the participation of marginalized populations: Case studies from a health service organization in Ontario, Canada - Montesanti, Stephanie. R.; Abelson, Julia; Lavis, John. N.; Dunn, James. R. (Health Promotion International, 2017)
We examined efforts to engage marginalized populations in Ontario Community Health Centers (CHCs), which are primary health care organizations serving 74 high-risk communities. Qualitative case studies of community participation in four Ontario CHCs were carried out through key informant interviews with CHC staff to identify: (i) the approaches, strategies and methods used in participation initiatives aimed specifically at engaging marginalized populations in the planning of and decision making for health services; and (ii) the challenges and enablers for engaging these populations. The marginalized populations involved in the community participation initiatives studied included Low-German Speaking Mennonites in a rural town, newcomer immigrants and refugees in an urban downtown city, immigrant and francophone seniors in an inner city and refugee women in an inner city. Our analysis revealed that enabling the participation of marginalized populations requires CHCs to attend to the barriers experienced by marginalized populations that constrain their participation. Key informants outlined the features of a ‘community development approach’ that they rely on to address the barriers to marginalized peoples' involvement by strengthening their skills, abilities and leadership in capacity-building activities. The community development approach also shaped the participation methods that were used in the engagement process of CHCs. However, key informants also described the challenges of applying this approach, influenced by the cultural values of some groups, which shaped their willingness and motivation to participate. This study provides further insight into the approach, strategies and methods used in the engagement process to enable the participation of marginalized populations, which may be transferable to other health services settings.

Aînés francophones et intervenants multiethniques en santé : un projet de formation interculturelle adapté aux collègues francophones canadiens - Parent, R.; Bouchard, Louise; Lebel, M. (Reflets, 2014)

Cognitive health initiative for Francophone seniors in the GTA: Options fo Service Models - Reflet Salvéo; Entité 4 (2017)
Like the general population, the Francophone population is aging and at a faster rate than the population as a whole. While the median age for the Ontario population is 40.1 years, it is 44 for Francophones, and the largest age categories among Francophones are 45-54 and 65 and over: almost one out of five Francophones is included in these age groups. Although the population of the Central Region, including the Greater Toronto Area (GTA), is somewhat younger, the median age of Francophones is still higher than that of the Central Region population as a whole (41.1 vs 39.4) 4. Yet services for people with cognitive disorders and their families and caregivers are fragmented and do not necessarily meet their needs or the demand for service. The situation for those seeking services in French is even worse. Language and culture are key factors in providing quality, safe care. Language barriers constitute a major obstacle for people with dementia and their caregivers and families. Many Francophones lose their second language and revert to their mother tongue as they age, particularly when they are under stress; this is especially true for people coping with dementia. It is essential that Francophones with dementia and their caregivers have equitable access to a continuum of culturally sensitive quality care in French at every stage of the dementia journey. To meet the growing needs of the GTA’s aging Francophone population, the two French language health planning entities, Reflet Salvéo and Entité 4, have partnered on a feasibility study on cognitive health together with the five GTA LHINs (Central West, Mississauga Halton, Toronto Central, Central and Central East), Centres d’Accueil Héritage (CAH) and the Glendon Centre for Cognitive Health. The purpose of the study is to develop options for service models for memory services, including a memory clinic, focussing on very early detection and intervention for mild cognitive impairment but also addressing the need for referrals and supports for those farther along on the dementia journey, and their caregivers. The initiative will build on work previously done on memory centre services in French and on initiatives developed and implemented in the five GTA LHINs. The models proposed will align with LHIN and provincial strategic priorities for dementia and services for seniors and focus on helping people experiencing cognitive decline to remain active participants in their communities for as long as possible. Methodology The first step was a brief analysis of a previous literature review along with a number of studies, reports and plans dealing with the impact of dementia and current service models as well as provincial and LHIN strategic priorities and initiatives for the next several years. Research was also conducted into the availability of services for people with dementia and their caregivers both overall and in French. The next steps involved gaining an overview of existing models and opportunities. As a second stage, interviews were held with LHIN representatives to develop a picture of LHIN priorities and approaches to dementia services in a context of profound system transformation affecting home and community care, primary care and putting the focus on patients, including seniors. Subsequently, following development of a discussion guide, interviews were conducted with health service providers, both those serving the population as a whole and those identified to provide services in French. Another important step was seeking the voice of the Francophone community through a mixture of focus groups and online surveys. Once options are developed, we will go back to providers and the community to seek their input and validate our recommendations. Work on the project as a whole was overseen and supported by a steering committee that included representatives of the two French language health planning entities and the five GTA LHINs as well as the Glendon Centre for Cognitive Health and Centres d’Accueil Héritage (CAH).
fs-ref-orig: Reflet Salvéo, & Entité 4. (2017). Cognitive health initiative for Francophone seniors in the GTA. Options fo Service Models. fs-code-orig: Reflet Salvéo-2017

Promotion de la santé et du bien-être des aînés d'expression anglaise du Québec. Un modèle communautaire (infographie) - Réseau communautaire de santé et de services sociaux / Community Health and Social Services Network (2019)
fs-ref-orig: Réseau communautaire de santé et de services sociaux. (2019). Promotion de la santé et du bien-être des aînés d'expression anglaise du Québec. Un modèle communautaire [infographie]. fs-code-orig: Réseau communautaire de santé et de services sociaux-2019

Étude de besoins sur les foyers de soins de longue durée dans la région du nord-est de l’Ontario - Rapport intérimaire - Réseau du mieux-être francophone du Nord de l’Ontario (2017)
Au début de l’année 2016, le Réseau du mieux-être francophone du Nord de l’Ontario (RMEFNO) a obtenu des fonds afin de mener une étude de besoins sur les foyers de soins de longue durée dans la région du nord-est de l’Ontario. Cette étude, se concluant en mars 2018, a été divisée en deux parties. Ce rapport résume, pour la région du nord-est, les résultats de la première partie, suite à la collecte de données au sujet des francophones et des foyers de soins de longue durée du Nord de l’Ontario. Ce rapport traite des défis auxquels font face les francophones en situation minoritaire résidant dans un foyer de soins de longue durée. Puis, on y discute de soins culturellement adaptés, accompagnés d’exemples de meilleures pratiques tirées de foyers de soins de longue durée de la province. Finalement, des recommandations sont apportées quant aux foyers de soins de longue durée du nord-est. Ces recommandations touchent l’identification et la désignation sous la Loi des services en français, ainsi que les soins culturellement adaptés.
Pages: 25

Needs Study: Long-Term Care Homes in the Northeastern Ontario Region - Interim report - Réseau du mieux-être francophone du Nord de l’Ontario (2017)
Early in 2016, the Réseau du mieux-être francophone du Nord de l’Ontario (RMEFNO) received funding to conduct a needs study regarding long-term care homes in the Northeastern Ontario Region. This two-part needs study is expected to be completed in March 2018. This report summarizes the results of Part 1, for the North East Region, based on the data collected on Francophones and long-term care homes in Northern Ontario. This report covers the challenges faced by Francophones in minority situations who reside in long-term care homes. As well, we touch on culturally appropriate care, and provide examples of best practices gathered from long-term care homes across the province. Finally, we make recommendations regarding long-term care homes in the North East. These recommendations address identification and designation under the French Language Services Act, as well as culturally appropriate care.
pages: 25

Guide de planification et de prestation des soins de longue durée en français. Leçons tirées du pavillon Omer Deslauriers de Bendale Acres et d'autres services de santé en français pour aînés au Canada - Réseau franco-santé du Sud de l’Ontario (2017)
pages: 106

Évaluation des services communautaires pour les aînées et aînés d’expression anglaise de Gaspésie-îles-de-la-Madeleine - Richardson, Mary (2019)
fs-ref-orig: Richardson, M. (2019). Évaluation des services communautaires pour les aînées et aînés d’expression anglaise de Gaspésie-îles-de-la-Madeleine. fs-code-orig: Richardson-2019

Pratique # 1 : Le Guide de mise en œuvre du mandat linguistique d’Actionmarguerite (Manitoba). - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (Dans: GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire., 2019)
Entre 2011 et 2013, en collaboration avec la SSF, le Conseil Communauté en santé du Manitoba et d’autres partenaires, Actionmarguerite a participé à un projet qui a permis de mieux comprendre la situation actuelle des services aux aînés francophones, puis d’agir pour améliorer la situation et enfin de transférer les connaissances afin que d’autres organisations puissent profiter de l’expérience acquise. La participation à ce projet témoigne de la valeur accordée par Actionmarguerite à l’innovation dans l’offre de services dans la langue officielle choisie par l’usager. C’est dans le cadre de cette initiative que le Guide de mise en œuvre du mandat linguistique d’Actionmarguerite, un guide bilingue à l’intention des gestionnaires a été conçu. Ce guide rappelle le contexte juridique en matière de langues de services et intègre les principaux documents qui encadrent la langue des services à l’échelle de la province, de l’ORSW et d’Actionmarguerite. Il précise les responsabilités des gestionnaires afin de s’assurer que les clients francophones soient servis dans la langue de leur choix.

Pratique # 2 : Une maisonnée francophone au Foyer Summerset (Île-du- Prince-Édouard) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (Dans: GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire., 2019)
Cette initiative de créer une aile francophone au sein du Foyer Summerset, dans un milieu majoritairement anglophone, vise à offrir des soins de longue durée dans la langue officielle de choix de l’usager·ère. Les aîné·es résident·es se sentent à l’aise de demander des services en français et un nombre suffisant de professionnel·les permet d’offrir tous les services en français, en incluant l’accueil.
fs-ref-orig: Savard, J., Savard, S., Van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., et Kubina, L.A. (2019). Pratique # 2 : Une maisonnée francophone au Foyer Summerset (Île-du- Prince-Édouard). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/repertoire_pratiques_novatrices.html fs-code-orig: Savard-2019a En 2025, ce document a fait l'objet d'une mise à jour du format, sans changement au contenu.

Pratique # 9 : Les Soins primaires communautaires pour aînés (Primary Care Outreach to Seniors) (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (Dans: GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire., 2019)
Le programme de Soins primaires communautaires pour aînés soutient les aînés et leurs proches aidants dans l’accès aux services sociaux et de santé requis (par exemple, la sécurité alimentaire, le logement, le revenu, le règlement, les services de soutien à domicile, le transport, l’éducation en matière des maladies chroniques, les activités sociales, physiques et récréatives). Un ou une gestionnaire de cas (soit un infirmier, infirmière ou un·e agen·te de santé communautaire) coordonne les services et les supports nécessaires et clarifie les rôles des fournisseurs de soins, facilitant ainsi la transition vers d’autres services. Il ou elle élabore, surveille et appuie la mise en œuvre des plans de soins coordonnés, et ce, dans un contexte de continuité relationnelle intervenant·e-client·e. Le service est offert en français et en anglais dans plusieurs centres de santé communautaires de la région d’Ottawa. Par la gestion de cas et la navigation des services, le programme facilite l’accès aux services en français qui existent.
Note: En 2025, ce document a fait l'objet d'une mise à jour du format, sans changement au contenu. fs-ref-orig: Savard, J., Savard, S., Van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., et Kubina, L.A. (2019). Pratique # 9 : Les Soins primaires communautaires pour aînés (Primary Care Outreach to Seniors) (Ontario). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/cahier_de_pratiques.html fs-code-orig: Savard-2019c

Améliorer l’accès des personnes âgées du Manitoba et de l’Île-du-Prince-Édouard aux services de santé en français - Société Santé en français (2014)
fs-ref-orig: Société Santé en français. (2014). Améliorer l’accès des personnes âgées du Manitoba et de l’Île-du-Prince-Édouard aux services de santé en français. Sommaire. fs-code-orig: Société Santé en français-2014b

Maintien à domicile : capacité d’offre de services communautaires actuels et futurs au Nouveau-Brunswick - Thériault, Danielle; Dupuis-Blanchard, Suzanne (Service Social, 2017)
La présente étude comporte trois objectifs : 1) déterminer l’état actuel des services offerts pour le maintien à domicile; 2) explorer la nature de la planification des services futurs pour le maintien à domicile; et 3) exposer les défis reliés aux services et les moyens qui s’offrent aux organismes pour que les services répondent le plus efficacement possible aux besoins des personnes âgées francophones. De type séquentiel exploratoire mixte, cette étude a permis de recueillir des données qualitatives pour bonifier des résultats quantitatifs. Quarante-neuf gestionnaires ont répondu au questionnaire en ligne et 11 entrevues ont été réalisées. Huit thèmes communs ont été dégagés en lien avec les objectifs, thèmes qui montrent une préoccupation pour la viabilité des services communautaires en maintien à domicile. Mots-clés : personnes âgées, maintien à domicile, planification, gestion, organismes communautaires, francophones